ANALISIS KEKUATAN MEMORANDUM OF UNDERSTANDING (MOU) SEBAGAI PERJANJIAN PENDAHULUAN DALAM HUKUM PERDATA INDONESIA - Noor Azizah; Iwan Riswandie; Istiana Heriani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The use of Memorandums of Understanding (MoUs) as initial agreements or contractual stages is growing in Indonesia, but their legal status remains valid. This research aims to examine the position of MoUs in Indonesian contract law, focusing on several valid agreement requirements as stated in Article 1320 of the Civil Code and the court's interpretation of MoUs in law enforcement. This research applies a normative approach in legal studies and case studies. The results show that an MoU can be legally binding if it meets the valid requirements of an agreement, namely agreement, the capacity of the parties, a clear object, and a legitimate cause. Several court decisions, such as Denpasar District Court Decision No. 419/PDT.G/2012/PN.DPS, recognize MoUs as preliminary agreements that give rise to legal obligations. However, if an MoU only contains a general understanding without clear obligations, then the MoU is considered merely a moral agreement without legal consequences. This research emphasizes the importance of clarity in establishing an MoU to provide legal certainty.